The Isolation of Sitronellal and Rhodinol from Lemongrass Oil Using Vacuum Distillation Fractination - Djafar, Fitriana; Hidayati, Hidayati (Balai Riset dan Standardisasi Industri Pontianak, 2010)
The main componenet of lemongrass oil that is sitronellal and rhodinol (sitronellol and geraniol) was isolated by using vacuum of distillation fraksinasi. Variably the research included the variable continue to, that is the sample weight (300 mL) and process time (4 hours); and the variable changed, that is the pressure (80, 95 and 100 mbar) and the temperature (145, 150, and 160o C). Results of the analysis of the ras material showed that lemongrass oil that came from Kota Panjang, Gayo Lues, Province Aceh had the content sitronellal that was high that is of 51.067% and rhodinol of 30.761%. The characteristics from lemongrass oil was yellow faded, the ray index 1.466, the specific gravity 0.889 solubility in alcohol 1:1 clear and the round of optics 19.15. The distillation sitronellal, 28.87% rhodinol (22.60% geraniol and 6.27% sitronellol) and 11% other component. The condition for the process that was good enough in the isolation sitronellol used distillation vacuum of fraksinasi with the temperature and the pressure that were low that is 145o C and 80 mbar. The condition for the process that was quite good in the isolation rhodinol was use to use vacuum of distillation fraksinasi in the temperature and the pressure that were not too high and or low that is 150o C and 95 mbar.